Conceptualising Spaces, Constructing Gender: Spatial Dimensions of Human Geography in Anita Nair's The Better Man - Garima Goyal
The purpose of this paper is to describe how Other Spaces or Different Spaces that are present in every society play an important role in regulating gender relation and gendered spaces. The focus will be on the South Indian writer Anita Nair’s novel The Better Man which is set in the fictitious village of Kaikurussi situated somewhere in North Malabar region. The nature of the argument lies in every human attempt to find inner peace and bliss, longing for true love and understanding of human relationships. The prospect is to explore women characters in analysing the notion of love and marriage and pre-marital, marital and extra-marital affairs in the novel extensively. Because of rapidly shifting ideas and practices space is represented as being fluid. The place in which the elements of the story are arranged is part visual and part virtual. It’s based on correlation between power of space and spatiality, between space and time and between historical and spatial imaginations. Subsequently, I will examine the text by implementing the First and Second principle of ‘Heterotopia’ (a concept elaborated by French Philosopher and Social Theorist Michel Foucault). Thus, in this paper I will discuss about the application of geography, knowledge and power that will represent, develop and resolve gender troubles and man-woman relationship attributing to Keralan society